The Effect of the Quality of Islamic Financial Reporting on Investor Investment Decisions - Nasution, Ferdi Dermawan; Nurlaila, Nurlaila (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
How does the quality of Islamic financial reporting affect investment decisions, in running a company it can be ensured that there are several goals that both management and owners want to achieve to attract the attention of investors. This research is a type of quantitative research using descriptive statistical methods and simple linear regression for hypothesis testing, Constanta 1.374 means that if the quality of presentation of Islamic financial statements is constant or fixed, then the decision in investment is 1.374. Regression direction coefficient 0.599 (positive value) means that if the quality of presentation of Islamic financial statements increases by 1 (unit), then the investment decision will increase by 0.599. The application of Islamic accounting in companies plays an important role in maintaining financial integrity and meeting the requirements set by Islamic principles.